SYSTEM PODATKÓW BEZPOŚREDNICH POLSKI MIĘDZYWOJENNEJ W PIERWSZYCH LATACH POLSKI LUDOWEJ - Witkowski, Andrzej (Zeszyty Prawnicze, 2016)
THE SYSTEM OF DIRECT TAXES OF INTERWAR POLAND IN THE FIRST YEARS OF THE PEOPLE’S REPUBLIC OF POLAND Summary The process of building the system of direct taxes of the People’s Republic of Poland was initiated in 1946. The tax legislation from before September 1939 which had been used until then was abolished. The urgency and scale of expenses which the Polish Committee of the National Liberation had to finance resulted in a decision in 1944 to temporarily use the prewar tax system despite the fundamental change of the political system of the state. Already in 1944 the prewar system of direct taxes was simplified by abolishing some taxes of smaller fiscal significance. The prewar acts of law on the turnover tax and income tax, after changes which deepened their fiscal nature, lost their binding force as of 1st January 1946. Moreover, the decree of 18th August 1945 on the employment tax replaced on 1st September 1945 the so far binding regulations of section II “Taxation of income from service emoluments, pensions and remunerations from hired work” of the act of 16th July 1920 on the national income tax. The system of national direct taxes supplemented the decree of 13th April 1945 on the emergency tax on war enrichment.